Սեֆյան դարաշրջանի սկզբնաղբյուրները որպես հայ ժողովրդի ԺԷ. – ԺԸ. դարերի պատմության աղբյուր - Մեշքանբարյանս, Ժիլբերտ (Մատենադարան)
The Safavid Iranian historical sources of the 17th-18th centuries, namely Iskandar Bek Torkaman Munshi’s Tarikhe Alam Araye Abbasi, Mirza Samia’s Tazkirat al-Muluk, Mohammad Rafi Ansari’s (or Mirza Rafia’s) Dastur al-Muluk” and Mohammad Mofid Mostofi Bafgi’s Mokhtasar-e Mofid, provide valuable information on the history of Armenia within the Safavid state. They reflect the main tendencies of the socio-economic and administrative policy of the Iranian authorities towards the Armenian people. They also characterize the consequences of the Persian rule in Armenia and the position taken by the local authorities on various issues concerning Armenians. Those sources enrich the history of Armenia in the given period with new data. Исторические источники Сефевидского Ирана XVII-XVIII веков (“Тарихе Алам Арайе Аббаси” Искандара Бека Торкамана Мунши, “Тазкират аль-Мулук” Мирзы Самиа, Мохаммадa Рафи Ансари или “Дастур аль-Мулук” Мирзы Рафии и “Мохтасар-е Мофид” Мохаммада Мофида Мостофи Бафги) содержат ценные сведения об Армении в составе государства Сефевидов. Они отображают основные тенденции социальнэкономической и административной политики иранских властей по отношению к армянскому народу. Они также характеризуют последствия персидского владычества для Армении, позицию местных властей по различным вопросам по отношению к армянам, и обогащают историю Армении этого периода новыми данными.
Keywords: միջազգային առցանց գիտաժողով; Պատմություն